Coarctation of the aorta: are genes relevant? - Francis, Catherine M (Journal of cardiovascular surgery, 2016)
In a busy clinic, it is easy to overlook genetic aspects of congenital heart disease. The complexity of genetic influence on disease makes it difficult to provide clear, accurate advice about recurrence risks and genetics to individual patients. This is particularly true of coarctation of the aorta, which appears sporadic in the majority of cases. We will see that in fact, genetics can play an important role in coarctation. We will review the current state of knowledge about the genetics of coarctation, encompassing syndromic and non-syndromic presentations, and consider the implications for clinical practice.